ART AND ESP INTEGRATION IN TEACHING UKRAINIAN ENGINEERS - David Pollard; Yuliia Olizko (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2019)
The article suggests art and ESP integration in a foreign language classroom at technical university. The authors describe five parts of the art and ESP integrated project "Water treatment" developed for teaching chemical engineers ESP at tertiary level. Each part of the project combines art such as poster drawing, writing a poem, creating a brand and making videos with ESP purposes. The results of the pedagogical experiment conducted at the National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute" (Igor Sikorsky KPI) proved the improvement of professional language, engineering creativity, intellectual engagement and collaboration skills of the students of the experimental group. The answers of the questionnaires conducted among the ESP teachers and students of Igor Sikorsky KPI showed their positive feedback about art and ESP integration. The issues of engineering creativity, active engagement, collaboration and authentic material usage were studied as components of multidisciplinary and multipurpose art and ESP integrated approach. The concluding part of the article outlines the main problems which can occur while integrating art and ESP in Ukraine such as lack of time and materials for exploring art, possible sсepticism towards art elements in ESP.